Aplikasi Sensor Accelerometer pada Handphone Android sebagai Pencatat Getaran Gempabumi secara Online: Rio Riantana, Hanief Beta, Waskita Cahya, Darsono - Rio Riantana, Rio Riantana; Hanief Beta, Hanief Beta; Waskita Cahya, Waskita Cahya; Darsono, Darsono (Jurnal Fisika dan Aplikasinya, 2025)
The method used is Cloud Computing, that is more practical and efficient.The purpose is to create a method of recording vibrations of earthquakes in realtime using the accelerometer sensor on android device. Android device used is Xiaomi 2 with processor Qualcomm Snapdragon 410 quad-cores @ 1.2 GHz with support for 4G LTE networks, gyroscop sensor, accelerometer, GPS support AGPSand GLONASS. All information received by android devices in the field will be sent to server in realtime per second. The monitoring system presented graphs vibration activity in realtime, location maps observed point, weather prediction maps, contour maps of land surface, and value of the magnitude of the acceleration of ground vibrations.